Clinical evaluation of anomalous aortic origin of a coronary artery (AAOCA). (16th June 2017) - Molossi, Silvana; Agrawal, Hitesh
Abstract: The clinical evaluation of patients with an anomalous aortic origin of a coronary artery (AAOCA), a congenital abnormality of the origin or course of a coronary artery that arises from the aorta, is challenging given its first presentation being sudden cardiac arrest in about half of the patients. Symptoms of chest pain, shortness of breath and syncope during exertion should be of concern in evaluating young athletes and nonathletes. The lack of abnormal signs on the physical exam and electrocardiogram further adds to the difficulty in establishing the diagnosis. Additional imaging with echocardiography, computed tomography angiography and/or cardiac magnetic resonance imaging (MRI) is often needed and establishes the diagnosis. High‐risk lesions include origin of the coronary artery from the opposite sinus of Valsalva, intramural course and ostial abnormalities (stenosis, hypoplasia). Functional studies should be performed to assess myocardial perfusion at rest and during stress, such as nuclear imaging, stress echocardiography and stress cardiac MRI.